Новые материалы к биографии Соломона Бейма - Белый, О.Б. (Материалы по археологии, истории и этнографии Таврии, 2003)
Ко второй четверти XIX в. заявило о себе и молодое поколение крымских караимов, представителей обеспеченных семей, успевших, в определенной мере, приобщиться к российской культуре и образованию. Среди этого круга осюбенно выделялся Соломон Бейм. После А.С.Фирковича он приобрел, пожалуй, наибольшую известность в среде российской и европейской научной общественности. Solomon Beim was bom in Chufut-Kale in 1817 (according to other data, in 1818 or 1819). He was weli educated. His contemporaries noted that besides Russian, Karaim and Hebrew ianguages, he knew French and German. M. Sultansky, a famous Karaim educator and religious figure was his teacher. In 1839 S. Beim made his debut with the history of the Karaims as a feiiow traveler of A. S. Firkovich in his first trip around Crimea to find Jewish antiquities. By the mid-1840s S. Beim carried out archaeological excavation in the neighbourhood of Chufut-Kaie, at the foothiii of Agarmush Mountain (Staruy Krym district), in 1852 at the meeting of Imperial Archaeological Society he presented his Program of Research of Jewish and Karaim antiquities of the Crimea. At the end of 1850s - the beginning of 1860s S. A. Beim being a gazzan of Karaim community in Chufut-Kaie, published several editions of his work on Chufut-Kale and the Karaims, where he expounded his view on the history of the Karaims in the Crimea. Besides, the conflict between A. S. Firkovich and S. Beim concerning the problems of studying and preserving Karaim monuments on the cemetery in Josaphat valley is referred to this period.